2021
DOI: 10.3389/fnagi.2021.750154
|View full text |Cite
|
Sign up to set email alerts
|

Medial Temporal Lobe Subregional Atrophy in Aging and Alzheimer's Disease: A Longitudinal Study

Abstract: Medial temporal lobe (MTL) atrophy is a key feature of Alzheimer's disease (AD), however, it also occurs in typical aging. To enhance the clinical utility of this biomarker, we need to better understand the differential effects of age and AD by encompassing the full AD-continuum from cognitively unimpaired (CU) to dementia, including all MTL subregions with up-to-date approaches and using longitudinal designs to assess atrophy more sensitively. Age-related trajectories were estimated using the best-fitted poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 121 publications
2
19
0
Order By: Relevance
“…Even though there is a ubiquitous and quite consistent trend of brain morphometry loss in wide parts of the cortex, the temporal lobe expressed the most significant effects even after multiple testing correction. Our findings are well in line with previous literature showing that the medial temporal lobe degenerates strongest in AD patients compared to typically aging subjects ( Jack et al, 1998 ; Chauveau et al, 2021 ). Here, we documented temporal tissue loss by more precise surface based morphometry and at a higher resolution of 360 cortical areas, which has become possible due to increased imaging quality in ADNI3 compared to previous ADNI studies ( Jack et al, 2008 ) and further developed software-aided image assessments.…”
Section: Discussionsupporting
confidence: 93%
“…Even though there is a ubiquitous and quite consistent trend of brain morphometry loss in wide parts of the cortex, the temporal lobe expressed the most significant effects even after multiple testing correction. Our findings are well in line with previous literature showing that the medial temporal lobe degenerates strongest in AD patients compared to typically aging subjects ( Jack et al, 1998 ; Chauveau et al, 2021 ). Here, we documented temporal tissue loss by more precise surface based morphometry and at a higher resolution of 360 cortical areas, which has become possible due to increased imaging quality in ADNI3 compared to previous ADNI studies ( Jack et al, 2008 ) and further developed software-aided image assessments.…”
Section: Discussionsupporting
confidence: 93%
“…Yet, our results suggest that typical aging may not sufficiently alter hippocampal volumes to allow detection of these relationships with hippocampal‐dependent tasks. Consistent with this idea, strong positive associations between hippocampal volumes and episodic memory scores have been observed for individuals with mild cognitive impairment and Alzheimer's disease, who often have more pronounced atrophy to the hippocampus than cognitively healthy older adults (Chauveau et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…Significant age‐related reductions have also been observed in nearby parahippocampal white matter, which includes axons of the perforant pathway (Stoub et al, 2012). In terms of macrostructure, both anterior and posterior gray matter volumes shrink with age, but show slightly different trajectories, with the posterior region showing an earlier inflection point and steeper decline thereafter (Chauveau et al, 2021; Langnes et al, 2020). Different trajectories of atrophy may partially explain why other longitudinal findings have demonstrated more robust anterior hippocampal volume change over time in older age (Chen et al, 2010); the years sampled may disproportionately impact the rate of change observed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the function of temporal lobe has a certain relationship with memory and emotion [25]. Previous studies have shown that the temporal lobe is the response area of cognitive impairment in Alzheimer's disease and even dementia, and it reflects the cognitive function network [26,27]. Therefore, this work can further infer that the spatial variability of microstate D network in the left temporal lobe can effectively reflect the cognitive level of PD patients.…”
Section: Discussionmentioning
confidence: 77%